Management Characteristics and Cost Stickiness: An Examination Based on Agency Theory - Abbas Ali Daryaei; Yasin Fattahi; Hamed Sadeqi; Ramazan Hasani (Environmental Energy and Economic Research, 2021)
Understanding how costs behave is a vital and critical issue for managers, management accountants, and financial analysts. Using agency theory, this paper addresses the empirical question of whether the management characteristics can help explain the cost stickiness as managerial behavior in the Tehran Stock Exchange. Utilizing a panel data regression model, we examined the data to determine the interaction impact of management characteristics as non-executive managers, managerial ability, overconfidence, and earnings management on cost stickiness of 165 firms, for the period 2009 to 2018. Results show that the entrenchment effects of non-executive managers increase the positive influences of managerial ability on overconfidence and as overconfidence increase, earnings management are also increasing consequently leads to an increase in cost stickiness. This means that when non-executive managers are excessively confident in their abilities, they are more likely to engage in opportunistic activities and earnings management. In these cases, managers report excessive cost overruns when there is a slight increase in company sales, resulting in increased cost stickiness. This study contributes by providing evidence on asymmetric cost behavior concerning management characteristics from one of the emerging economies. Further, the study extends the very few studies on the relationship between management characteristics and cost stickiness.